1999
DOI: 10.1152/ajpheart.1999.276.1.h215
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency component of the heart rate variability spectrum: a poor marker of sympathetic activity

Abstract: The low-frequency component of the heart rate variability spectrum (0.06–0.10 Hz) is often used as an accurate reflection of sympathetic activity. Therefore, interventions that enhance cardiac sympathetic drive, e.g., exercise and myocardial ischemia, should elicit increases in the low-frequency power. Furthermore, because an enhanced sympathetic activation has been linked to an increased propensity for malignant arrhythmias, one might also predict a greater low-frequency power in animals that are susceptible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
164
0
8

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(188 citation statements)
references
References 20 publications
16
164
0
8
Order By: Relevance
“…A mounting number of studies indicates that this hypothesis is flawed on several points, and it is more probable that the 0.1-Hz oscillation in heart rate provides an index of baroreflex gain (5,38,39). Our model supports this hypothesis and may explain why some stimuli such as coronary occlusion, which increases mean SNA levels, was associated with reductions in power at 0.1 Hz in heart rate (19). Studies in humans add further support to this hypothesis, where stimulation of carotid baroreceptors by neck suction at two frequencies (0.1 and 0.2 Hz) induced a low-frequency oscillation in heart rate or blood pressure only if baroreflex sensitivity was normal, and that low baroreflex sensitivity was associated with reduced variability at this low frequency (38).…”
Section: Discussionsupporting
confidence: 66%
“…A mounting number of studies indicates that this hypothesis is flawed on several points, and it is more probable that the 0.1-Hz oscillation in heart rate provides an index of baroreflex gain (5,38,39). Our model supports this hypothesis and may explain why some stimuli such as coronary occlusion, which increases mean SNA levels, was associated with reductions in power at 0.1 Hz in heart rate (19). Studies in humans add further support to this hypothesis, where stimulation of carotid baroreceptors by neck suction at two frequencies (0.1 and 0.2 Hz) induced a low-frequency oscillation in heart rate or blood pressure only if baroreflex sensitivity was normal, and that low baroreflex sensitivity was associated with reduced variability at this low frequency (38).…”
Section: Discussionsupporting
confidence: 66%
“…As previously described (Gron®er et al 1999), the LF/(LF + HF) ratio and delta wave activity displayed opposite variations, with LF/(LF + HF) ratio decreases preceding the increases of delta wave activity by about 10 min. However, there are a number of studies demonstrating that the LF/HF ratio and the normalized LF/(LF + HF) ratio as quanti®ed by spectral analysis of R±R intervals do not accurately re¯ect changes in sympatho-vagal balance (Brown et al 1993;Eckberg 1997;Houle and Billman 1999). As this subject is still matter of debate (Malliani 1999), care should be taken in relating the present data on heart rate variability to the activity of the autonomic nervous system.…”
Section: Discussionmentioning
confidence: 90%
“…Heart rate variability was determined by spectral analysis of R±R intervals and the ratio of low frequency power to low frequency power plus high frequency power [LF/(LF + HF)] was calculated. Despite some controversies (Eckberg 1997;Houle and Billman 1999), this ratio is considered as an index of the sympatho-vagal balance (Malliani 1999).…”
Section: Introductionmentioning
confidence: 99%
“…1H), may reflect nonlinear interactions between the two nervous systems. The presence of interactions between the two nervous systems has been reported in many experimental studies (13,19,24). For example, Miyamoto et al (24) found that ␤-adrenergic blockade with intravenous propranolol administration in anesthetized rabbits decreased the dynamic gain of the transfer function during vagal stimulation, which may suggest that decreased SNS may blunt the HR responses to the PNS activation.…”
Section: Discussionmentioning
confidence: 97%
“…Some suggest that LF activity is largely due to the SNS and that the ANS balance can be reliably calculated as the ratio of LF to HF (15,20,27). Current prevailing evidence, on the other hand, suggests that the vagal contributions to LF are as significant as those of the sympathetic nervous activities; consequently, the LF-to-HF ratio would be an approximation and not an accurate measure of the ANS balance (7,12,13). Although initial successes have been obtained in estimating sympathovagal balance by calculating a ratio between LF and HF PSD (2,16,19,32), clinical use of this method has not been widespread, mainly because the LF-to-HF ratio is not a close enough approximation of the autonomic balance, for the reasons stated above.…”
mentioning
confidence: 99%